The Bauhaus and the Russian avant-garde - Bonnefoit, Régine (Munich, London, New York: Prestel, 2017)
In 1995, Jean-Claude Marcadé declared that research into the relationship between the Bauhaus and the Russian avant-garde was essentially nonexistent. In recent years, new studies on the Hungarian Bauhaus master László Moholy-Nagy and his compatriots Lajos Kassák, Béla Uitz, and Alfréd Kemény, have yielded fresh insights into the development and transfer of ideas. The essay provides an overview of the most important mediators, publications, and private and state initiatives that undertook to promote exchange between the two sides.
Keywords: Bauhaus; Russian avant-garde